THE RELATIONSHIP OF BREAKFAST HABITS WITH HEMOGLOBIN LEVELS IN CLASS XI STUDENTS AT SMA NEGERI 7 DENPASAR - Satwikha Dewi, I Gusti Agung Ayu; Dwijastuti, Ni Made Sri; Septiasari, Ni Putu Senshi; Widiantari, Ni Putu; Eka Putri, Ni Putu Puniari (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
Introduction: Hemoglobin levels are a clinical parameter in routine hematology examinations which are used to determine whether there are health problems. Adolescents need to pay attention to hemoglobin levels because hemoglobin levels are crucial for supporting the physical, mental and academic well-being of adolescents during this important phase of their growth and development. Method: This research method is observational research with a cross sectional approach. This research was conducted at SMA Negeri 7 Denpasar, Wednesday 24 May 2023. The sampling technique used was purposive sampling with a sample size of 42 students in class XI of SMA Negeri 7 Denpasar. Results: There were 8 students in class Students who did not have breakfast had normal and high hemoglobin levels, while students who had breakfast had low, normal and high hemoglobin levels. The results of the analysis using the Somers'D test showed that there was no relationship between breakfast habits and hemoglobin levels with p value = 0.188 or p 0.05. Conclusion: Breakfast habits do not directly affect hemoglobin levels.Keywords : breakfast, hemoglobin, teenager